Sistem Informasi 717 Advertising Berbasis Web - Muh, Ismail; Saing, Ferdiansyah; Annur, Rahmat Hidayat Annur (Jurnal Sintaks Logika, 2021)
717 Advertising is a printing company located in the city of Parepare. Has made many products. 717 Advertising also offers flower arrangement and other services, but still uses an offline ordering system. This information system is built using PHP and MySQL. In addition, using Gammu as an sms banking confirmation process to check automatic payments. Information System Design 717 This web-based advertising has capabilities that can be accessed easily and everywhere. The resulting output is a regular purchase report, filtered by month or year. Starting from inputting product data, by admin, and consumers can access wherever consumers are and payment transactions with an automatic payment system.